Combination of phosphine and carbon dioxide on the control of Rhyzopertha dominica (F.) - Martinazzo, Ana Paula; Faroni, Lêda Rita D'Antonino; Berbert, Pedro Amorim; Reis, Fernando Pinheiro (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this research was to evaluate the effect of low levels of phosphine associated with atmospheres containing high levels of carbon dioxide (CO2) on the effective control of all life stages of the insect Rhyzopertha dominica (F.). To this purpose, fumigations were carried out using a synthetic atmosphere containing 21% of CO2 and 79% of N2 associated with the following levels of phosphine: 0.25, 0.50, and 0.75 g m-3. Results were compared with mortality rates achieved with ambient air containing zero and 1.00 g m-3 of phosphine. All tests were carried out using three levels of exposure time (24, 72, and 120 hours), and one level of temperature and relative humidity, 29°C and 60%, respectively. Analyses of the results indicated that increasing the exposure time resulted in an increase in mortality rates in all tests conducted with synthetic and ambient air. Effective control of all life stages of R. dominica was only achieved with atmospheres containing 21% of CO2 associated with phosphine concentration levels of 0.50 and 0.75 g m-3 in 120 hours exposure time. In general, eggs and adults were the most susceptible insect stages, and pupae the most resistant.